2007
DOI: 10.1021/ac0706271
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Stimulation of Platelet Nitric Oxide Production Indicated by Quantitative Monitoring of the Communication between Cells in the Bloodstream

Abstract: ATP is a recognized stimulus of nitric oxide synthase and is released from red blood cells (RBCs) upon deformation. The objective of this work is to demonstrate that RBCs stimulate nitric oxide production in platelets by employing a continuous flow analysis system in which the stream contains both RBCs and platelets. Here, two drugs known to improve blood flow in vivo (pentoxyfilline and iloprost) are shown to increase both the release of RBC-derived ATP and the production of platelet-derived NO. A flowbased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
0
29
0
1
Order By: Relevance
“…23 Moreover, it has been demonstrated that erythrocytes are capable of releasing adenosine triphosphate by mechanical deformation or pharmacologically, thus favoring nitric oxide release by activated platelets. 24 In contrast, anemic patients with ACSs, except those with very low hematocrit, do not seem to benefit from administration of blood transfusions that, on the contrary, are associated with a worse outcome 25 ; the negative impact of blood transfusions in patients presenting with anemia and suspected ACS has been confirmed and ascribed to the change in shape and deformability of stored erythrocytes, 25 which probably release a larger amount of ADP, thus further decreasing platelet responsiveness to antiplatelet drugs.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, it has been demonstrated that erythrocytes are capable of releasing adenosine triphosphate by mechanical deformation or pharmacologically, thus favoring nitric oxide release by activated platelets. 24 In contrast, anemic patients with ACSs, except those with very low hematocrit, do not seem to benefit from administration of blood transfusions that, on the contrary, are associated with a worse outcome 25 ; the negative impact of blood transfusions in patients presenting with anemia and suspected ACS has been confirmed and ascribed to the change in shape and deformability of stored erythrocytes, 25 which probably release a larger amount of ADP, thus further decreasing platelet responsiveness to antiplatelet drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has also been shown to inhibit the release of nitric oxide-stimulating ATP from erythrocytes, further contributing to vascular dysfunction. 5,6 …”
Section: Biochemistry Of Diabetic Complications Prior To 2005mentioning
confidence: 99%
“…The ATP released by deformed RBCs may help these cells to communicate not only with endothelial cells but also with other neighbors, such as platelets. Platelets that sense a local increase in [eATP] (due to RBCs or other platelets) also produce NO (19), and this is key to preventing the further recruitment of other platelets to the activated platelets and thus averting obstruction of narrow vessels. A third type of cell-to-cell communication is that which occurs when [eATP] is strongly increased, for example, as happens after cell damage.…”
mentioning
confidence: 99%